Indian identity narratives and the politics of security - Commuri, Gitika; Sage eBooks (Delhi ; London : SAGE, 2010)
This book provides a fresh insight into the role of identity in international and national relations and policy. It analyses identity conceptions and state behaviour, arguing that identities constitute a crucial element of state interest, both in terms of end goals and strategies.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: National characteristics, East Indian; Nationalism -- India; India -- Ethnic relations -- Political aspects; India -- Foreign relations -- Pakistan; Pakistan -- Foreign relations -- India; India -- Foreign relations -- China; China -- Foreign relations -- India; Electronic books